Mother–offspring recognition in the domestic cat: Kittens recognize their own mother's call. Issue 5 (3rd March 2016) - Szenczi, Péter; Bánszegi, Oxána; Urrutia, Andrea; Faragó, Tamás; Hudson, Robyn
ABSTRACT: Acoustic communication can play an important part in mother‐young recognition in many mammals. This, however, has still only been investigated in a small range mainly of herd‐ or colony‐living species. Here we report on the behavioral response of kittens of the domestic cat, a typically solitary carnivore, to playbacks of "greeting chirps" and "meows" from their own versus alien mothers. We found significantly stronger responses to the chirps from kittens' own mother than to her meows or to the chirps or meows of alien mothers. Acoustic analysis revealed greater variation between vocalizations from different mothers than for vocalizations from the same mother. We conclude that chirps emitted by mother cats at the nest represent a specific form of vocal communication with their young, and that kittens learn and respond positively to these and distinguish them from chirps of other mothers and from other cat vocalizations while still in the nest. © 2016 Wiley Periodicals, Inc. Dev Psychobiol 58: 568–577, 2016.